Beta-cell failure rather than insulin resistance is the major cause of abnormal glucose tolerance in Africans: insight from the Africans in America study - Thomas Hormenu; Christopher W DuBose; Lilian S Mabundo; Joon Ha; Arthur Sherman; Anne E Sumner; M C Sage Ishimwe; Annemarie Wentzel; Elyssa M Shoup; Nana H Osei-Tutu; Arielle C Patterson; Hadi Bagheri (BMJ Open Diabetes Research & Care)
Introduction Uncertainties exist on whether the main determinant of abnormal glucose tolerance (Abnl-GT) in Africans is β-cell failure or insulin resistance (IR). Therefore, we determined the prevalence, phenotype and characteristics of Abnl-GT due to β-cell failure versus IR in 486 African-born blacks (male: 64%, age: 38±10 years (mean±SD)) living in America.Research design and methods Oral glucose tolerance test were performed. Abnl-GT is a term which includes both diabetes and prediabetes and was defined as fasting plasma glucose (FPG) ≥5.6 mmol/L and/or 2-hour glucose ≥7.8 mmol/L. IR was defined by the lowest quartile of the Matsuda Index (≤2.98) and retested using the upper quartile of homeostatic model assessment of insulin resistance (HOMA-IR) (≥2.07). Abnl-GT-IR required both Abnl-GT and IR. Abnl-GT-β-cell failure was defined as Abnl-GT without IR. Beta-cell compensation was assessed by the Disposition Index (DI). Fasting lipids were measured. Visceral adipose tissue (VAT) volume was obtained with abdominal CT scan.Results The prevalence of Abnl-GT was 37% (182/486). For participants with Abnl-GT, IR occurred in 38% (69/182) and β-cell failure in 62% (113/182). Compared with Africans with Abnl-GT-IR, Africans with Abnl-GT-β-cell failure had lower body mass index (BMI) (30.8±4.3 vs 27.4±4.0 kg/m2), a lower prevalence of obesity (52% vs 19%), less VAT (163±72 vs 107±63 cm2), lower triglyceride (1.21±0.60 vs 0.85±0.42 mmol/L) and lower FPG (5.9±1.4 vs 5.3±0.6 mmol/L) and 2-hour glucose concentrations (10.0±3.1 vs 9.0±1.9 mmol/L) (all p<0.001) and higher DI, high-density lipoprotein (HDL), low-density lipoprotein particle size and HDL particle size (all p<0.01). Analyses with Matsuda Index and HOMA-IR yielded similar results. Potential confounders such as income, education, alcohol and fiber intake did not differ by group.Conclusions Beta-cell failure occurred in two-thirds of participants with Abnl-GT and may be a more frequent determinant of Abnl-GT in Africans than IR. As BMI category, degree of glycemia and lipid profile appeared more favorable when Abnl-GT was due to β-cell failure rather than IR, the clinical course and optimal interventions may differ.Trial registration number NCT00001853.